2015
DOI: 10.1039/c5dt01713k
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and ionic platinum compounds containing a cyclometallated chiral primary amine: synthesis, antitumor activity, DNA interaction and topoisomerase I–cathepsin B inhibition

Abstract: The synthesis and preliminary biological evaluation of neutral and cationic platinum derivatives of chiral 1-(1-naphthyl)ethylamine are reported, namely cycloplatinated neutral complexes [PtCl{(R or S)-NH(2)CH(CH(3))C(10)H(6)}(L)] [L = SOMe(2) ( 1-R or 1-S ), L = PPh(3) (2-R or 2-S), L = P(4-FC(6)H(4))(3) (3-R), L = P(CH(2))(3)N(3)(CH(2))(3) (4-R)], cycloplatinated cationic complexes [Pt{(R)-NH(2)CH(CH(3))C(10)H(6)}{L}]Cl [L = Ph(2)PCH(2)CH(2)PPh(2) (5-R), L = (C(6)F(5))(2)PCH(2)CH(2)P(C(6)F(5))(2) (6-R)] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 79 publications
(157 reference statements)
1
15
0
Order By: Relevance
“…As the results show, complexes A and B are more effective than C and D against two cancer cells. This refers to higher biological activity of primary amine metallacycles than secondary amines due to the possibility of being involved in hydrogen bonds through the NH 2 group . Although the IC 50 values of complexes against MCF‐7 cells are close to or higher than cisplatin, they are comparable with other similar palladium complexes …”
Section: Resultsmentioning
confidence: 99%
“…As the results show, complexes A and B are more effective than C and D against two cancer cells. This refers to higher biological activity of primary amine metallacycles than secondary amines due to the possibility of being involved in hydrogen bonds through the NH 2 group . Although the IC 50 values of complexes against MCF‐7 cells are close to or higher than cisplatin, they are comparable with other similar palladium complexes …”
Section: Resultsmentioning
confidence: 99%
“…[24,25] However,noc orrelation was observed between the cytotoxicity in cancer cells and Pt accumulation within the series of compounds, asp reviously reported for other metal complexes. revealed that cellular accumulationf or all platinum cyclometallated compounds was significantly higher than for cisplatin.…”
mentioning
confidence: 64%
“…Previous evidence gathered by our group on different related sets of cyclometallated Pt II and Pt IV complexes extensively revealed that cellular accumulation for all platinum cyclometallated compounds was significantly higher than for cisplatin . However, no correlation was observed between the cytotoxicity in cancer cells and Pt accumulation within the series of compounds, as previously reported for other metal complexes .…”
Section: Methodsmentioning
confidence: 99%
“…The antitumor properties of cyclometallated Pt(II) compounds have been studied by several groups in the last few years . These compounds displayed high stability and increased lability of the leaving groups, which was attributed to the strong trans effect of C‐donor ligands.…”
Section: N‐heterocyclic Carbenes and Cyclometallated Platinum Complexesmentioning
confidence: 99%
“…These compounds displayed high stability and increased lability of the leaving groups, which was attributed to the strong trans effect of C‐donor ligands. Recently, Albert et al . discussed and designed several cyclometallated Pt(II) compounds ( 101 – 106 ; Figure ) containing a chiral primary amine ligand (( R or S )‐1‐(1‐naphthyl)ethylamine), and a coordination compound containing two non‐cyclometallated chiral ( R ) amines ( 107 ; Figure ).…”
Section: N‐heterocyclic Carbenes and Cyclometallated Platinum Complexesmentioning
confidence: 99%